FaPOD27 functions in the metabolism of polyphenols in strawberry fruit (Fragaria sp.) - Yeh, Su-Ying; Huang, Fong-Chin; Hoffmann, Thomas; Mayershofer, Mechthild; Schwab, Wilfried (Frontiers in Plant Science, 2014)
The strawberry (Fragaria × ananassa) is one of the most preferred fresh fruit worldwide, accumulates numerous flavonoids but has limited shelf life due to excessive tissue softening caused by cell wall degradation. Since lignin is one of the polymers that strengthen plant cell walls and might contribute to some extent to fruit firmness monolignol biosynthesis was studied in strawberry fruit. Cinnamoyl-CoA reductase (CCR), cinnamyl alcohol dehydrogenase (CAD), and a peroxidase (POD27) gene were strongly expressed in red, ripe fruit whereas a second POD gene was primarily expressed in green, immature fruit. Moreover, FaPOD27 transcripts were strongly and constitutively induced in fruits exposed to Agrobacterium infection. Gene expression levels and enzymatic activities of FaCCR and FaCAD were efficiently suppressed through RNAi in FaCCR- and FaCAD-silenced strawberries. Besides, significantly elevated FaPOD transcript levels were detected after agroinfiltration of pBI-FaPOD constructs in fruits. At the same time, levels of G-monomers were considerably reduced in FaCCR-silenced fruits whereas the proportion of both G- and S-monomers decisively decreased in FaCAD-silenced and pBI-FaPOD fruits. Development, firmness, and lignin level of the treated fruits were similar to pBI-intron control fruits, presumably attributed to increased expression levels of FaPOD27 upon agroinfiltration. Additionally, enhanced firmness, accompanied with elevated lignin levels, was revealed in chalcone synthase-deficient fruits (CHS-), independent of down- or up-regulation of individual and combined FaCCR, FaCAD, and FaPOD genes by agroinfiltration, when compared to CHS-/pBI-intron control fruits. These approaches provide further insight into the genetic control of flavonoid and lignin synthesis in strawberries. The results suggest that FaPOD27 is a key gene for lignin biosynthesis in strawberry fruit and thus to improving the firmness of strawberries.